TRADER CRYPTO SEBAGAI PERUBAHAN MINAT PROFESI GENERASI Z DI ERA POSTMODERNISME - Sahita, Fathur Rahmani; Manurung, Patricia Mora; Rahman, Tazkia Aulia; Ferdiansyah, Muhammad; Safitri, Dini (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2022)
Technological developments are inseparable from changes in the life and mindset of each individual, as well as generation z. Generation Z is a generation that is very close and able to follow the flow of technological change. One of those technological changes is online investments such as crypto. The era of postmodernism is an era or mass in which everything that is not commonplace or taboo in the modernism era becomes normal for humans. This is what makes researchers draw the formulation of the problem, namely how Crypto Traders as Generation Z Professional Interest Changes in the Era of Postmodernism. With the aim of knowing Crypto Traders as Generation Z Professional Interest Changes in the Era of Postmodernism. The research method used is descriptive qualitative research method with data collection using interviews and data analysis model Miles and Hubermen. The results of this study found that the speed and intelligence of Generation Z in keeping up with technological changes made crypto traders a change of professional interest in the era of postmodernism.